Food, environment and health : a guide for primary school teachers - Williams, Trefor; Moon, Alysoun; Williams, Margaret (Geneva : World Health Organization, 1990)
Gives educators a highly practical collection of facts, advice, projects, games, illustrations, stories, and sample questions for use in teaching children the importance of healthy habits, particularly concerning food, personal hygiene and the home environment. Details range from advice on how to start a school garden or design a class growth chart to instructions for a game of germ warfare that illustrates how pathogens invade the human body. Throughout, emphasis is placed on simple, imaginative tools for correcting errors of food safety, nutrition, and personal hygiene commonly found in developing countries. The book consists of seven self-contained teaching units which can be used in any sequence. Various chapters deal with the practical aspects of storing and handling food safely, making water fit to drink, disposing of wastes, and maintaining a healthy home environment. Teachers are also given guidance on explaining to children exactly why the body needs water, the types of food needed by the body to stay healthy, and the means by which infection and disease can be spread through a community. Liberally illustrated, the book contains numerous suggestions for involving school children in practical activities that will reinforce what they learn and help them to appreciate the relevance of their new knowledge to their lives outside the school. Participation by parents and community leaders in many of these activities is also encouraged as yet another route for spreading the book's simple yet vital messages
Preface -- Introduction -- Unit 1. food and the body -- Unit 2. Keeping food safe -- Unit 3. a safe water supply -- Unit 4. Safe collection and disposal of waste -- Unit 5. Personal hygiene -- Unit 6. Insects, pest and domestic animals -- their role in spreading disease -- Unit 7. A healthy home environment
Keywords: Health education -- in infancy & childhood; Nutrition -- education; Environmental health; School health services; Teaching; Developing countries